2019
DOI: 10.1152/physrev.00031.2018
|View full text |Cite
|
Sign up to set email alerts
|

Myelin in the Central Nervous System: Structure, Function, and Pathology

Abstract: Oligodendrocytes generate multiple layers of myelin membrane around axons of the central nervous system to enable fast and efficient nerve conduction. Until recently, saltatory nerve conduction was considered the only purpose of myelin, but it is now clear that myelin has more functions. In fact, myelinating oligodendrocytes are embedded in a vast network of interconnected glial and neuronal cells, and increasing evidence supports an active role of oligodendrocytes within this assembly, for example, by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
315
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 453 publications
(330 citation statements)
references
References 694 publications
8
315
0
7
Order By: Relevance
“…Oligodendrocytes (OLGs) are specialized cells of the central nervous system (CNS) that generate the axon enwrapping myelin sheath, which enables rapid and efficient saltatory conduction and provides metabolic axonal support (Stadelmann, Timmler, Barrantes‐Freer, & Simons, ). During development, cells of the OLG lineage originate as bipolar and migratory OLG progenitor cells (OPCs) within distinct regions of the CNS (Miller, ; Naruse, Ishizaki, Ikenaka, Tanaka, & Hitoshi, ; Ono et al, ; Richardson, Kessaris, & Pringle, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oligodendrocytes (OLGs) are specialized cells of the central nervous system (CNS) that generate the axon enwrapping myelin sheath, which enables rapid and efficient saltatory conduction and provides metabolic axonal support (Stadelmann, Timmler, Barrantes‐Freer, & Simons, ). During development, cells of the OLG lineage originate as bipolar and migratory OLG progenitor cells (OPCs) within distinct regions of the CNS (Miller, ; Naruse, Ishizaki, Ikenaka, Tanaka, & Hitoshi, ; Ono et al, ; Richardson, Kessaris, & Pringle, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rajani et al reported that mature oligodendrocytes are decreased, which implies abnormal myelination. In the CNS, MBP and NF200 are the critical components of myelin and axons, and their integrity plays an important role in maintaining the conduction of nerve fiber bundles . In our study, cognitive decline and myelin degeneration were observed after mice were infused with Ang ‐ for 28 days.…”
Section: Discussionmentioning
confidence: 56%
“…Rajani et al 38 of myelin and axons, and their integrity plays an important role in maintaining the conduction of nerve fiber bundles. 39 In our study, cognitive decline and myelin degeneration were observed after mice were infused with Ang Ⅱ for 28 days. Under NR administration, the cognitive function of mice was significantly improved, and the degradation of myelin was repressed.…”
Section: Discussionmentioning
confidence: 61%
“…The persistence of an appropriate myelin plasticity over the lifespan, moreover, means that axon wrapping by the OLs is modified depending on functional demand [8]: indeed the wrapping of OL cytoplasm around the axons determines the thickness of the myelin sheath and the internode length [9]. Moreover, OLs are metabolically active and functionally connected to the axon via cytoplasm-rich "myelinic channels", through which the OL takes up blood-derived glucose and delivers glycolysis products (pyruvate/lactate) to myelinated axons via monocarboxylate transporters (MCT1 and MCT2) [10,11]. WM plasticity is influenced by a variety of regulators, including daylight rhythm, gender and pregnancy, voluntary physical exercise, environmental and social environment, motor learning, and cognitive training [3].…”
Section: White Matter Plasticity In the Adult Brain Ageing Cognitivmentioning
confidence: 99%